Rancang Bangun Aplikasi pengelola Data Pekerja Berbasis Website Di BRI Kendari Cabang Samratulangi - Auliya Rahman Asdar; Muhammad Akbar Asad Ishaq; Rizal Adi Saputra (Jurnal Teknologi Informasi dan Multimedia, 2023)
The large number of workers managed makes it difficult for BRI officers at the Samratulangi branch to manage them. Management of employee data at the Samratulangi branch of BRI was previously managed via Microsoft Excel. Management carried out manually causes several problems, including the difficulty of identifying workers whose work terms have expired and the number of workers being managed is quite large and takes a long time. This problem can be solved by building a worker data management application. Application development is carried out using the prototype method. In this research, the application is designed to be able to manage workers' data well, be able to manage workers' attendance, know the active status of workers, and be able to issue Specified Time Work Agreement Decree in a timely manner. Based on the prototype method, researchers carry out the communication stage to obtain information about the problems faced by users. At the Quick plan and Modeling quick design stage, researchers began to design the UML and display in prototype form to then create a User Interface. Next, at the Feedback and Delivery stage, researchers ask for feedback and suggestions regarding the application that has been created which will then be developed and improved according to user input. So the system is created so that users can run the system according to their needs. Based on the test results using a blackbox, the system is designed according to its function and use.